Transactions at play - Clark, Cindy Dell (Play & culture studies ;, 2009)
When players play, there is a transactional process at work, whether for children on a teeter-totter or pandas playing with peers. In this edited volume, nine experts on play show how play transactions are an important dynamic of play across cultures, agegroups, even species. A rich array of play contexts is evident across the nine chapters, encompassing varied continents, age groups, and sorts of players. The play processes of giant pandas, of home-visiting therapists, of Polynesian women, and of autistic kids are included here. The healthy interchange of ideas about play, one of the hallmark.